Bioaugmentation and biostimulation of a South African coal-based Technosol as a mine rehabilitation strategy - Van Coller, Cari (Department of Chemical Engineering, 2024)
Annually, over 70 million tonnes of material are added to coal waste dumps in South Africa. To alleviate the environmental and social burdens of unsightly mine waste dumps, improved management of existing discarded materials and new wastes, and fertile soils for land rehabilitation are essential. To achieve successful mine closure and restore derelict land, sustainable mine rehabilitation schemes aligned with circular economy principles should be prioritized. A proposed method for effective and controlled resource management based on waste valorisation involves repurposing the major coal ash fraction of coal waste, provided it has been classified as benign in terms of acidification, salinisation and metal deportment, to fabricate a soil (Technosol) by amending it with a suitable organic waste source to provide both soil structure and nutrient availability and establishing an appropriate microbial consortium. This study investigated the improvement of Technosol fertility through biostimulation and bioaugmentation. By introducing a diverse microbial community, typically associated with healthy soils and initially absent in mine waste, the establishment of self-sustaining fertile topsoils to rehabilitate disturbed mining areas is accelerated. The Technosol used in this investigation was fabricated from ultrafine coal tailings amended with malt residue from a local brewery. The fabricated soil was inoculated with a commercially available soil inoculum (EM Pro-Soil) and amended with different dosages of malt residue (0%, 2.5%, 5% and 7% w/w). Eragrostis tef (teff) plants were grown in each of the treatments, including a non-inoculated control. Seasonal teff growth was mimicked by performing a second trial of plant growth studies. Soil health, quality and fertility were determined from assessment of soil physical, chemical, and biological properties that inferred Technosol feasibility for implementation. Bioaugmentation increased nutrient availability for plant growth through organic material degradation. From plant-microbe interactions, soil inoculation resulted in increased microbial biomass and metabolic activity compared to non-inoculated Technosols. Bioaugmentation and biostimulation with more than 2.5 wt.% malt residue (MR) reduced metal(loid) solubility. Technosol microbiome diversity following inoculation depended on applied amendment dosage and was positively influenced by alkaline soil pH, lowered salinity, water permeation, and vegetational growth. Soil pH was regulated biogenically through MR application as biostimulant for microbial respiration. Teff biomass production and inflorescence were favoured in warmer conditions as a result of accelerated microbial activities and photosynthesis. The effect of microbial inoculation was more evident during the second plant growth trial with higher bacterial and archaeal abundances. Here we evaluated the succession of the microbial community by qPCR analysis of 16S rRNA V3 to V4 regions. Following vegetation and inoculation, abundances of nirK gene encoding nitrite reductase denitrification enzymes were augmented in Technosols fabricated with higher dosages of MR, suggesting enhanced nitrogen uptake. Vegetation in inoculated Technosols amended with 5 wt.% MR assisted remediation of soil iron and sulfur to suitable levels, reduced leaching, favoured seedling emergence with temporal effects, and showed the greatest potential for nitrogen cycling from nifH gene abundances that correlated to enhanced phosphorus uptake. The results supported the feasibility of implementing Technosols as topsoils to reduce socio-economic and environmental impacts of coal mine related processes, by targeting the Sustainable Development Goals (SDGs) 9, 11, and 15.